A Comparison of Learning Outcomes in Computer Subject between Web-Blended Learning and Traditional Learning of the Ninth Grade Students - Arokha, Karn; Liumthaisomg, Khachakrit; Kidkarn, Rattakorn (Ratchaphruek Journal, 2015)
This study aimed 1) to develop a web-based lesson by using the integrated method, 2) to determine the effectiveness of a web-based lesson, 3) to compare the learning achievement and skills of students in setting the computer and 4) to study the students’ satisfaction and learning behaviors, the research samples were the three classes of the ninth grade students of the academic year 2012, in total of 60 students. The statistical analysis of the data were mean, standard deviation, percentage, statistical hypothesis and statistic Hotelling T2 Results of the study were as follows: (1) a web-based lesson by using the integrated method, it showed its efficiency of 86.75 / 84.50, (2) its effectiveness index was 0.6398 and (3) students who learned a web-based lesson by using the blended method showed the level of statistical significance. 05 in their average achievement skills computer which was higher than students who learned with the traditional learning and (4) students satisfaction in learning was in the highest level and their learning behavior was in the high one.